Hubungan Gaya Pengasuhan dan Struktur Kekuatan Keluarga dengan Risiko Penyalahgunaan NAPZA: Alkohol pada Remaja di SMA Kecamatan Kalisat Kabupaten Jember (Relationship between Parenting Style, Family Power Structure and Risk of Drug Abuse: Alcohol in Adol - Lina Nur Khumairoh; Latifa Aini Susumaningrum; Mulia Hakam (Pustaka Kesehatan, 2018)
Adolescence is one of population at risk of drug abuse. One kind of drug is alcohol. A family has avery important role in the risk of alcohol abuse in adolescents. A family simultaneously has structureand function which very important for adolescent development. This study aimed to analyze therelationship between parenting style, family power structure and risk of drug abuse: alcohol inadolescents in the high school of Kalisat Sub-district of Jember Regency. The research method wasanalytical observation with cross sectional approach. Respondents were 249 adolescents withmultistage random sampling. Independent variable is parenting style, family power structure; andrisk of drug abuse: alcohol is dependent variable. The data were analyzed by chi square (α = 0,05).The result showed that significant relationship between parenting style and risk of drug abuse:alcohol (p value 0,000); significant relationship between family power structure and risk of drugabuse: alcohol (p value 0,004). Family power can protect adolescents from the risk of alcoholabuse. There are rules must be believed and performed by adolescents. Furthermore, family canperform parenting with balance of freedom and responsibility of adolescents. However, parents shallconsider the personality of their adolescents.Keywords: risk of alcohol abuse, parenting style, family power structure